2008
DOI: 10.1182/blood-2007-08-108050
|View full text |Cite
|
Sign up to set email alerts
|

CD28 provides T-cell costimulation and enhances PI3K activity at the immune synapse independently of its capacity to interact with the p85/p110 heterodimer

Abstract: Activation of PI3K is among the earliest signaling events observed in T cells after conjugate formation with antigenpresenting cells (APCs). The relevant PI3K catalytic isoform and relative contribution of the TcR and CD28 to PI3K activity at the immune synapse have not been determined unequivocally. Using a quantitative imaging-based assay, we show that the PI3K activity at the T cell-APC contact area is dependent on the p110␦, but not the p110␥, isoform of PI3K. CD28 enhanced PIP3 production at the T-cell sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
142
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(149 citation statements)
references
References 84 publications
5
142
2
Order By: Relevance
“…It has been shown that engagement of the TCR and CD28 leads to the translocation and activation of PKCθ to the lipid rafts in the SMAC (22). This process also involves other signaling molecules, including leukocyte-specific protein tyrosine kinase lck, Vav, Zap-70, and PI3K (23,24).…”
Section: Common Pi3k/pkb/nf-κβ Pathwaysmentioning
confidence: 99%
“…It has been shown that engagement of the TCR and CD28 leads to the translocation and activation of PKCθ to the lipid rafts in the SMAC (22). This process also involves other signaling molecules, including leukocyte-specific protein tyrosine kinase lck, Vav, Zap-70, and PI3K (23,24).…”
Section: Common Pi3k/pkb/nf-κβ Pathwaysmentioning
confidence: 99%
“…58 Mutation of the CD28 YMNM motif residues Y (i.e., disruption of Grb2 and PI3K binding) and M residues (i.e., loss of PI3K binding alone) interferes with the induction of IL-2 in T-cell hybridomas, 46,[59][60][61] while in vivo responses showed either no 62 or partial dependency on CD28-PI3K. 63,64 Part of this confusion may be due to the generation of sufficient D-3 lipids by high affinity peptide agonist binding to the TCR, and by the fact that CD28 can enhance PIP 3 production at the immunological synapse independently of its YMNM PI3K-recruitment motif, 51 perhaps by increasing the efficiency of conjugate formation, and indirectly TCR signaling. The use of high affinity peptide ligands could obviate the need for supplemental CD28 induction of PIP 3 .…”
Section: Cd28 Co-signaling Pathwaysmentioning
confidence: 99%
“…Class IB PI3K deficiency affects T-cell development and function. 50,51 The SH2-domain of the p85 regulatory subunit of PI3K binds to the CD28 pYMNM motif. [44][45][46][47] This facilitates localization of the p110 catalytic subunit in the plasma membrane, and allows for receptor mediated activation.…”
Section: Cd28 Co-signaling Pathwaysmentioning
confidence: 99%
“…The p110d isoform is expressed mainly by immune cells and is an important signaling protein for lymphocytes. Although there are several studies on the role of PI3Ks in immune responses (16)(17)(18)(19), few have focused on their role in immunologic memory. Recently, there has been accumulating data suggesting that PI3K may also play an important role in the maintenance and recruitment of memory T cells (20,21).…”
Section: The Journal Of Immunologymentioning
confidence: 99%